Rekonstruksi dan Digitalisasi Taman Sebagai Upaya Peningkatan Kesejahteraan Masyarakat di Desa Mlorah - Ardela Putri Amalia; Nira Fitryani; Niken Hefa Zakkiya; Shafa Diva Syaharani; Hendra Maulana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The reconstruction of the village park is an urgent need in strengthening local identity, improving the quality of life of the community and its environment. The location of the park located on the edge of the Janeng Dam in Mlorah Village is quite well maintained and there are trees that make the environment cool, but it lacks attractiveness because there are no vehicle facilities. The purpose of this community service activity is to achieve the SDGs indicators in order to create a healthier environment, support the digitalization of education, and preserve the environment. The method in implementing the activity is Participatory Action Research. The results of this park reconstruction and digitalization activity are park social media accounts and inorganic waste management into park facilities in the form of biopores, park direction signs, and playgrounds